Chronic osteomyelitis of the hand by Mycobacterium kansasii in an immunocompromised patient - Cerna, Jorge Adrián Garza; Zarazúa, Raúl Omar Martínez; Flores, Everardo Valdes; García, M. Mauricio Manuel Perez; Rivera, Gabriel Angel Mecott (International Surgery Journal, 2021)
Atypical mycobacteria are pathogens that uncommonly infect the hand. These organisms are capable of causing extensive bone damage in the hand. Mycobacterium kansasii is a slow growing non-tuberculous Mycobacterium. It is the second most common non-tuberculous Mycobacterium that mainly affects the hand and joints. Immunosuppressed patients are more likely to develop infection. Because extrapulmonary involvement of M. kansasii is rare, skin and soft tissue infections are infrequent; osteomyelitis is even rarer. Immunosuppressed patients are more likely to develop infection. A history of trauma is frequent. There is a delay in diagnosis antibiotics have been given with no response. Imaging studies are recommended in the diagnostic approach, with magnetic resonance imaging being the best option to show bone and soft tissue involvement. Infected tissue culture has greater sensitivity for diagnosis. Treatment for musculoskeletal involvement consists of multiple susceptibility-based antibiotics and antiretroviral therapy in HIV coinfection, combined with surgical management with incision and drainage.